2005
DOI: 10.1057/palgrave.ejis.3000520
|View full text |Cite
|
Sign up to set email alerts
|

Social ties, knowledge sharing and successful collaboration in globally distributed system development projects

Abstract: Traditionally, the main focus of the information system (IS) literature has been on technical aspects related to system development projects. Furthermore, research in the IS field has mainly focused on co-located project teams. In this respect, social aspects involved in IS projects were neglected or scarcely reported. To fill this gap, this paper studies the contribution of social ties and knowledge sharing to successful collaboration in distributed IS development teams. Data were drawn from two successful gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(69 citation statements)
references
References 41 publications
(33 reference statements)
2
66
0
1
Order By: Relevance
“…This is supported by Janowicz and Noorderhaven (2002) who found that both collaboration and mutual trust among individuals in the organization were crucial factors in knowledge sharing and transfer. Similarly, the findings by Kotlarsky and Oshri (2005) found social ties and knowledge sharing are positively associated with successful collaboration. As mentioned earlier, relational psychological contract revolves around trust, loyalty and mutuality (Atkinson, 2007;Lester et.…”
Section: Knowledge Sharing and Relational Capitalmentioning
confidence: 64%
“…This is supported by Janowicz and Noorderhaven (2002) who found that both collaboration and mutual trust among individuals in the organization were crucial factors in knowledge sharing and transfer. Similarly, the findings by Kotlarsky and Oshri (2005) found social ties and knowledge sharing are positively associated with successful collaboration. As mentioned earlier, relational psychological contract revolves around trust, loyalty and mutuality (Atkinson, 2007;Lester et.…”
Section: Knowledge Sharing and Relational Capitalmentioning
confidence: 64%
“…It has also been found that social ties, including trust and rapport, would have a positive relationship on knowledge sharing. It has also been proposed that guanxi would promote knowledge transfer between the two firms (Kotlarsky & Oshri, 2005). So, we hypothesize that:…”
Section: Cultural Factormentioning
confidence: 98%
“…Collaboration can improve relationships between team members (Nelson and Cooprider 1996). Additionally, effective team performance may derive from successful collaboration between team members (Jassawalla and Sashittal 1999;Kotlarsky and Oshri 2005). In summary, prior studies indicated that team interaction is playing an important enabling role in team performance (Trist 1981).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 95%